Kanglaite inhibits EMT caused by TNF-α via NF-κΒ inhibition in colorectal cancer cells - Shi, Guiling (Oncotarget, 2017)
Tumor necrosis factor-alpha is a critical pro-inflammatory cytokine produced by macrophages and was once considered an anti-tumor agent. However, a low dose of tumor necrosis factor-alpha can cause epithelial mesenchymal transition, angiogenesis and metastasis. NF-κΒ contributes to epithelial mesenchymal transition induced by tumor necrosis factor-alpha. Kanglaite, an extract from the Coix lacryma-jobi (adlay) seed, is an NF-κΒ inhibitor. The aim of this study was to investigate whether Kanglaite could inhibit epithelial mesenchymal transition caused by tumor necrosis factor-alpha using four colorectal cancer cell lines, HCT106, HCT116, LoVo and CT26. Our results showed that tumor necrosis factor-alpha -mediated activation of NF-κΒ, caused changes in epithelial mesenchymal transition -related protein expression, and increased migration and invasion in all four cell lines. However, these effects were inhibited by Kanglaite when used in combination with tumor necrosis factor-alpha. In a subcutaneous tumor model of CT26, tumor necrosis factor-alpha enhanced the tumorigenic ability of the cells, and again this was inhibited by Kanglaite. However, treatment with Kanglaite alone caused almost no inhibition of epithelial mesenchymal transition -mediated tumor growth, when cells were pretreated with tumor necrosis factor-alpha prior to injection. These results suggest that Kanglaite inhibits tumor necrosis factor-alpha -mediated epithelial mesenchymal transition in colorectal cancer cell lines via inhibition of NF-κΒ.